Screening of effective markers for Mesophilic bacterium growth using factorial experimental design - Ahmad, Mani Malam; Mohd Azoddien, Abd. Aziz; Mohd Zahari, Mior Ahmad Khusairi; Abu Seman, Mazrul Nizam; Jami, Mohammed Saedi (Science & Engineering Research Support soCiety, 2017)
Attempts to gain an insight and present bacterial growth pattern from OVAT perspectives are quite defective and strenuous. The present study aimed at evaluating this concept from the different perspective by evaluating factors with more impacts on the growth of a mesophilic bacterium, Bacillus cereus (ATCC 14579) in a batch type medium of orbital shake flasks. Screening of linear and interactions effects of parametric markers was evaluated by two level (24) factorial design of experiment (DOE). Growth was found to respond significantly to nutrient concentration coupled with other independent variables. The factorial models established from experimental design to investigate the individual and interactions effects toward the response within the selected variables of nutrient concentration (4-16 g l-1), temperature (30 oC – 42 oC), agitation (140 rpm-200 rpm) and acclimatization time (24 hours-72 hours). These were statistically validated using analysis of variance (ANOVA). The results revealed that the model terms were all significant with F-value of 251.07 at (p =0.004). The model term having the most significant effect on the response was nutrient concentration. And the magnitude of the influence is in the ascending order A > B > AB > C > AC. Based on the R2 and adjusted R2 the estimated model terms spell high degree of relationship between observed and predicted values, thus the prediction ability of the models is maintained. It could, therefore, be concluded that nutrient concentration, temperature and acclimatization time were variables that greatly limit growth at a specific range.